PENGARUH DESENTRALISASI FISKAL, FISKAL STRES, DAN KINERJA KEUANGAN TERHADAP PERTUMBUHAN EKONOMI (Studi Empiris Pada Kota dan Kabupaten di Provinsi Jawa Timur) - Ira Puspita Sari; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2021)
This study aims to examine the effect of fiscal decentralization, fiscal stress, financial performance on economic growth in cities and districts in East Java. This type of research is quantitative. The data used are secondary data obtained indirectly through intermediaries, such as other people or documents. Secondary data in this study are the financial statements of the City / Regency governments in East Java. Next, the research variables were analyzed using multiple linear regression analysis in order to determine the direct or indirect effect of the variables on the research model. The results of the analysis show that the variables of fiscal decentralization, fiscal stress and financial performance significantly influence economic growth. In increasing economic growth in the era of fiscal decentralization, regional governments are given the authority to regulate and increase regional autonomy, namely fiscal needs and fiscal capacity (goods and services) so that the government is able to optimize its sources of economic revenue.Keywords: Fiscal Decentralization, Fiscal stress, Financial Performance, Economic Growth.